Monte Carlo simulation methods-based models for analyzing the kinetics of drug delivery from controlled release systems - Saúl Jiménez-Jiménez; Salomón Cordero-Sánchez; José-Gerardo Mejía-Hernández; David Quintanar-Guerrero; Luz-María Melgoza-Contreras; Rafael Villalobos-García (Brazilian Journal of Pharmaceutical Sciences)
Abstract Pharmaceutical controlled-release formulations are systems developed by a set of unit operations to achieve a satisfactory combination between a drug and excipients to allow its gradual release. These devices must simultaneously meet criteria for stability, biocompatibility, safety, efficacy, scalability at industrial volumes, and technological efficiency for drug release. Controlled-release systems (CRSs) must release drugs in a way that maintains an adequate concentration in the organism, a requirement that is challenging to meet in practice. Even though novel CRSs may be designed with new materials as excipients, new drugs, or emerging manufacturing technologies, the mechanisms for drug release continue to be governed by a set of similar physicochemical phenomena such as diffusion, swelling, or erosion. These phenomena are too complex to be analyzed by numerical methods; however, they are relatively accessible by probabilistic models especially the Monte Carlo simulation. In this review, we discuss key findings related to the use of this probabilistic method for analyzing the drug-controlled release process in different pharmaceutical devices. Based on this evidence, we propose their potential application in the characterization of new drug-controlled release systems, synergy with other computational methods, and their capability to be adapted for in vivo or in vitro kinetic analysis.